All Days 2010
DOI: 10.2118/133497-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Injection Rate of A New Chelate That Can Be Used To Stimulate Carbonate Reservoirs

Abstract: Different chelating agents were used as alternatives for HCl in matrix acidizing to remove near wellbore damage and create wormholes in carbonate formations. Previous studies have demonstrated the use of ethylenediaminetetraacetic acid (EDTA), hydroxy ethylenediaminetetraacetic (HEDTA) and glutamic acid-N,N-diacetic acid (GLDA) as an alternative for HCl to stimulate carbonate reservoirs. The main problem with EDTA and HEDTA is the low biodegradability.GLDA was introduced as alternative for HCl for stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The chelating agents were EDTA, HEDTA, and GLDA. GLDA is a newly introduced chelating agents, it was effective in stimulating calcite cores (Mahmoud et al 2010a). Those fluids will be used at pH values of 11 and 4 using Berea and Bandera sandstone cores at 300 o F. Therefore, the objectives of this study are to: (1) determine the compatibility of EDTA, HEDTA, and GLDA with both Berea and Bandera sandstone cores at pH of 11, (2) Determine the compatibility of HEDTA and GLDA at pH of 4 with both Berea and Bandera cores, and (3) Indentify the best chelating agent that can be used to stimulate both Berea and Bandera sandstone core at pH values of 11, and 4.…”
Section: Introductionmentioning
confidence: 99%
“…The chelating agents were EDTA, HEDTA, and GLDA. GLDA is a newly introduced chelating agents, it was effective in stimulating calcite cores (Mahmoud et al 2010a). Those fluids will be used at pH values of 11 and 4 using Berea and Bandera sandstone cores at 300 o F. Therefore, the objectives of this study are to: (1) determine the compatibility of EDTA, HEDTA, and GLDA with both Berea and Bandera sandstone cores at pH of 11, (2) Determine the compatibility of HEDTA and GLDA at pH of 4 with both Berea and Bandera cores, and (3) Indentify the best chelating agent that can be used to stimulate both Berea and Bandera sandstone core at pH values of 11, and 4.…”
Section: Introductionmentioning
confidence: 99%
“…EDTA and HEDTA chelating agents' structure that will be used in this study are shown in Fig. Mahmoud et al (2011aMahmoud et al ( , 2011bMahmoud et al ( , 2011cMahmoud et al ( , 2011dMahmoud et al ( , and 2012 investigated the use of different chelating agents as stand-alone stimulation fluids in carbonate and sandstone formations at high temperatures as alternatives to conventional acids such as HCl and organic acids. Fig.…”
Section: Chelating Agentsmentioning
confidence: 99%
“…They were followed by Frenier and co-workers (2001Frenier and co-workers ( , 2003Frenier and co-workers ( , 2004 who introduced HEDTA. Mahmoud et al used GLDA to stimulate carbonate (LePage et al 2011;Mahmoud et al 2011aMahmoud et al , 2011b and sandstone formations (Mahmoud et al 2015) to remove carbonates and oxides minerals. Reyes et al (2013) examined a new chelant.…”
Section: Introductionmentioning
confidence: 99%